10.1093/gao/9781884446054.013.7002292402 (Inactive DOIs, 2018)
BACKGROUND: Rheumatoid arthritis (RA) is a chronic autoimmune disease characterized by progressive joint destruction and significant impairment of health-related quality of life (HRQoL). The receptor activator of nuclear factor-κB ligand (RANKL)/osteoprotegerin (OPG) pathway plays a pivotal role in bone metabolism and joint destruction in RA. However, the clinical value of serum OPG and RANKL levels for identifying low physical HRQoL status in RA patients remains unclear. This study aimed to develop and internally validate a nomogram model incorporating serum OPG and RANKL to estimate the probability of low physical HRQoL status in RA patients. METHODS: This retrospective cross-sectional study enrolled 324 RA patients from January 2022 to December 2025. Patients were randomly divided into training (n = 227) and internal validation (n = 97) cohorts at a 7:3 ratio. HRQoL was assessed using the Medical Outcomes Study 36-Item Short-Form Health Survey (SF-36), with low physical HRQoL status defined as SF-36 Physical Component Summary (PCS) score < 40 at the assessment time point. Serum OPG and RANKL levels were measured by enzyme-linked immunosorbent assay. Univariate and multivariate logistic regression analyses were performed to identify factors associated with low physical HRQoL status. Age and sex were included as clinically important adjustment variables, HAQ-DI was incorporated to account for functional disability, and the RANKL/OPG ratio was not entered into the primary multivariate model together with its components to avoid mathematical collinearity. A nomogram was constructed and internally validated using split-sample assessment, receiver operating characteristic (ROC) curves, calibration plots, and decision curve analysis (DCA). RESULTS: Among 324 patients, 138 (42.6%) had low physical HRQoL status. In the primary multivariate model, HAQ-DI (OR = 2.18, 95%CI: 1.48-3.22, P < 0.001), serum RANKL (OR = 1.76, 95%CI: 1.25-2.48, P = 0.001), serum OPG (OR = 0.75, 95%CI: 0.59-0.96, P = 0.022), DAS28-ESR (OR = 1.48, 95%CI: 1.05-2.08, P = 0.025), disease duration (OR = 1.36, 95%CI: 1.04-1.78, P = 0.024), and CRP (OR = 1.24, 95%CI: 1.01-1.52, P = 0.042) were associated with low physical HRQoL status after adjustment for age and sex. The nomogram demonstrated excellent discrimination with an AUC of 0.881 (95%CI: 0.835-0.927) in the training cohort and 0.864 (95%CI: 0.792-0.936) in the internal validation cohort. Calibration curves showed good agreement between predicted and observed probabilities. DCA confirmed substantial clinical net benefit across clinically relevant threshold probabilities. CONCLUSIONS: This study developed and internally validated a nomogram model integrating serum OPG and RANKL levels, functional disability, inflammatory activity, and disease duration for identifying low physical HRQoL status in RA patients. The model demonstrates robust discrimination, calibration, and clinical utility, providing clinicians with a practical tool for individualized risk stratification and facilitating earlier supportive and disease-control interventions.